Does training in motivational interviewing for community pharmacists improve outcomes for methadone patients? A cluster randomised controlled trial. (3rd July 2013) - Jaffray, Mariesha; Matheson, Catriona; Bond, Christine M.; Lee, Amanda J.; McLernon, David J.; Johnstone, Allan; Skea, Lucy; Davidson, Bruce
Abstract Objectives Feasibility of pharmacist delivered motivational interviewing (MI) to methadone patients has been demonstrated, but its efficacy is untested. This study aimed to determine whether pharmacists trained in MI techniques can improve methadone outcomes. Methods A cluster randomised controlled trial by pharmacy, with community pharmacies across Scotland providing supervised methadone to >10 daily patients, aged >18 years, started on methadone <24 months. Pharmacies were randomised to intervention or control. Intervention pharmacists received MI training and a resource pack. Control pharmacists continued with normal practice. Primary outcome was illicit heroin use. Secondary outcomes were treatment retention, substance use, injecting behaviour, psychological/physical health, treatment satisfaction and patient feedback. Data were collected via structured interviews at baseline and 6 months. Key findings Seventy‐six pharmacies recruited 542 patients (295 intervention, 247 control), mean age 32 years; 64% male; 91% unemployed; mean treatment length 9 months. No significant difference in outcomes between groups for illicit heroin use (32.4% cf. 31.4%), although within‐groups use reduced (P < 0.001); treatment retention was higher in the intervention group but not significantly (88% cf. 81%; P = 0.34); no significant difference between groups in treatment satisfaction, although this improved significantly in intervention (P < 0.05). More intervention than control patients said pharmacists had 'spoken more, ' which approached statistical significance (P = 0.06), and more intervention patients found this useful (P < 0.05). Conclusions Limited intervention delivery may have reduced study power. The intervention did not significantly reduce heroin use, but there are indications of positive benefits from increased communication and treatment satisfaction.